2017
DOI: 10.3346/jkms.2017.32.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Factors Related to Clinical Severity of Acute Gastroenteritis in Hospitalized Children after the Introduction of Rotavirus Vaccination

Abstract: We aimed to investigate epidemiology and host- and pathogen-related factors associated with clinical severity of acute gastroenteritis (AGE) in children after rotavirus vaccination introduction. Factors assessed included age, co-infection with more than 2 viruses, and virus-toxigenic Clostridium difficile co-detection. Fecal samples and clinical information, including modified Vesikari scores, were collected from hospitalized children with AGE. The presence of enteric viruses and bacteria, including toxigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
6
20
0
Order By: Relevance
“…A significant observation in this study was also the relatively higher detection rate of HAdV infection, as compared to a previous study based on serologic assays from Valencia [ 46 ], and to reports from other continents [ 53 55 ] that suggest the existence of a geographic variability of the virus prevalence, as well as the important contribution of the HAdVs to the mixed infections. A similar rate of HAdV detection was reported from Korea during the years 2012–2013 [ 6 ], but it is noteworthy that the relative high prevalence for HAdV observed in this study could have also been determined by the presence in the stools of non-enteric types that could occasionally be excreted from respiratory source, and detected by the assay used, directed to amplify a conserved portion of the hexon-coding gene, common for all the HAdV. Thus, the molecular characterization is a crucial step to define the species of HAdV mainly involved in diarrhea and to understand the true contribution to the AGE.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A significant observation in this study was also the relatively higher detection rate of HAdV infection, as compared to a previous study based on serologic assays from Valencia [ 46 ], and to reports from other continents [ 53 55 ] that suggest the existence of a geographic variability of the virus prevalence, as well as the important contribution of the HAdVs to the mixed infections. A similar rate of HAdV detection was reported from Korea during the years 2012–2013 [ 6 ], but it is noteworthy that the relative high prevalence for HAdV observed in this study could have also been determined by the presence in the stools of non-enteric types that could occasionally be excreted from respiratory source, and detected by the assay used, directed to amplify a conserved portion of the hexon-coding gene, common for all the HAdV. Thus, the molecular characterization is a crucial step to define the species of HAdV mainly involved in diarrhea and to understand the true contribution to the AGE.…”
Section: Discussionsupporting
confidence: 80%
“…Rotaviruses (RV) are the main cause of mortality due to diarrhea in those under 5 years old, preventable with the vaccination [ 4 , 5 ]. Yet, despite a significant reduction after RV vaccine introduction in 2006, hospitalizations for infantile AGE of viral etiology continued to be reported [ 6 9 ]. The increasing use of more powerful diagnostic systems in the last few years, as the conventional polymerase chain reaction (PCR) or high-throughput technologies, for the amplification and identification of virus genomes in stool samples, has resized the study of the agents involved in childhood AGE [ 7 , 10 , 11 ], and changed significantly the pathogen spectrum of community-acquired gastroenteritis [ 6 , 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for the overall greater reduction in the sensitivity among rectal swabs without visible pigment to detect bacteria than to detect viruses was the high rate of detection of C. difficile, which was detected in 2.8% more swabs with pigment visible than in those without visible pigment. As young children are often colonized with C. difficile (15,19) with low pathogen loads, the C. difficile density might more often be below the detection limit in swabs without visible feces. This hypothesis is supported by evidence that among toxin-positive C. difficile-infected patients, toxin concentrations are significantly higher and C T values are significantly lower than those among carriers (20) and by our findings of the significantly reduced sensitivity of rectal swabs without pigment to detect C. difficile.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis has shown that heterogeneity continues to be present even in stratification cases under the conditions noted previously [25][26][27][28]. This heterogeneity in the studies weakens the "evidence base" [29], which is why studies with a large sample and a precise management protocol and more objective measurement methods are needed. It is also necessary to divide the sample into subgroups according to the elements already mentioned which may change the results.…”
Section: Discussionmentioning
confidence: 96%